2022
DOI: 10.1002/bit.28055
|View full text |Cite
|
Sign up to set email alerts
|

Engineered yeast for efficient de novo synthesis of 7‐dehydrocholesterol

Abstract: The synthesis of vitamin D3 precursor 7-dehydrocholesterol (7-DHC) by microbial fermentation has much attracted attention owing to its advantages of environmental protection. In this study, Saccharomyces cerevisiae was engineered for a de novo biosynthesis of 7-DHC. First, seven essential genes (six endogenous genes and one heterologous gene) were overexpressed, and the ROX1 gene (heme-dependent repressor of hypoxic genes) was knocked out. The resulting strain produced 82.6 mg/L 7-DHC from glucose. Then, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The most recent experience to date in this regard was carried out by Qu et al (2022) who constructed an engineered yeast for the highly efficient production of 7‐DHC through a systems metabolic engineering approach, which included different genetic modifications: overexpression of essential genes (six endogenous and one heterologous), gene knock out ( ROX1 and GDH1 ), gene copy increase using the Ty1 transposon ( ERG1 and DHCR24 ), and competitive pathway inhibition using CRISPRi (CRISPR interference). Using this combined approach, they obtained a 7‐DHC titer of 365.5 mg/L in a shake flask, and of 1328 mg/L in a 3‐L bioreactor with a specific titer of 114.7 mg/g dry cell weight, the highest values obtained to date.…”
Section: Vitamin D Production In Yeastmentioning
confidence: 99%
“…The most recent experience to date in this regard was carried out by Qu et al (2022) who constructed an engineered yeast for the highly efficient production of 7‐DHC through a systems metabolic engineering approach, which included different genetic modifications: overexpression of essential genes (six endogenous and one heterologous), gene knock out ( ROX1 and GDH1 ), gene copy increase using the Ty1 transposon ( ERG1 and DHCR24 ), and competitive pathway inhibition using CRISPRi (CRISPR interference). Using this combined approach, they obtained a 7‐DHC titer of 365.5 mg/L in a shake flask, and of 1328 mg/L in a 3‐L bioreactor with a specific titer of 114.7 mg/g dry cell weight, the highest values obtained to date.…”
Section: Vitamin D Production In Yeastmentioning
confidence: 99%
“…4AD is a highly valuable steroid precursor commonly used to produce a broad spectrum of therapeutically important hormones, such as testosterone and estradiol. Recently, 4AD synthesis via microbial sterol biotransformation has made considerable progress at the industrial scale. However, the starting substrates (sterols) need to be obtained from natural resources, and the low water solubility of sterols reduces their bioavailability during steroid production . In addition to classical biotransformation approaches, de novo steroid synthesis from simple carbon sources can be employed to obtain steroidal compounds in an environmentally friendly process. However, to the best of our knowledge, no studies regarding the microbial de novo synthesis of 4AD have been reported to date. 4AD biosynthesis involves a nonlinear pathway constituting coordinated reactions mediated by two promiscuous enzymes: 17α-hydroxylase/17,20-lyase ( CYP17A1 ), responsible for 17α-hydroxylation and a subsequent 17α,20-lyase reaction (C17-C20 bond cleavage), and 3β-hydroxysteroid dehydrogenase (3β- HSD ), an isomerase responsible for converting Δ5-steroids to corresponding Δ4-isomers (i.e., the Δ5-alkene double bonds at 5,6-carbons are converted to Δ4-bonds at 4,5-carbons; Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Such switch in the cellular phenotype is a complex natural trait of some organisms, e.g., secondary metabolite producing bacteria and fungi in response to certain growth-essential nutrient limitation. , It is, however, not simply transferable to other species, many of which commonly respond to nutrient limitation by reducing the metabolic activities to a bare minimum or even entering into quiescence. , Thus, avoiding nutrient limitation using inducible synthetic regulation to repress metabolic pathways linked to growth appears appealing. In a common eukaryotic production host, yeastSaccharomyces cerevisiae, switches in cellular phenotypes during cultivation processes have been achieved by using inducible promoters or transcription factors, a heterologous quorum sensing system coupled to RNA interference for gene expression control, an auxin-responsive protein degradation system, and Clustered Regularly Interspaced Short Palindromic Repeats interference (CRISPRi) triggered from an inducible promoter . The approaches are conceptually promising for developing efficient producer strains and processes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the quorum sensing-coupled RNA interference and auxin-inducible degradation targeted to single growth-essential enzymes have been demonstrated to deliver substantially improved product titers (i.e., para-hydroxybenzoic acid titer by 41% 28 and nerodiol titer by 36% 29 ). However, these previous attempts have compromised the target activities already prior to the intended switch, 29,31 relied upon induction not possible during glucose utilization, 30 interfered with the native proteasome, 29 or have been inefficient in counteracting native regulation. 32 We demonstrate here a novel inducible synthetic regulation system in S. cerevisiae addressing the previous challenges.…”
Section: ■ Introductionmentioning
confidence: 99%